Investigating Cyclic and Pushover Performance of Different Metallic Yielding Dampers - Ali Mohammad Rousta; Sohrab Shoja; Masoud Amin Safaei Ardakani (Journal of Rehabilitation in Civil Engineering)
One of the most widely used and applicable solutions for limiting the damages of earthquakes to steel structures is using Metallic Yielding Dampers as a type of passive devices to dissipate the received energy. Maintaining a proper balance in the design of these devices is a delicate matter as each of the different types have advantages and disadvantages. In this research, different types of metallic dampers are compared using finite element simulation which is performed by means of ABAQUS package. Modeling process is described and verified by comparing the results to a previously published experimental paper on the subject. For assuring more accuracy a mesh convergence analysis is performed to determine the suitable mesh size. Afterwards, cyclic and pushover analysis are performed on each damper and results are presented and discussed. Effective stiffness and damping of each damper, both general and average, is extracted using proper equations and finite element results. Finally, for deeper understanding of dampers behavior, internal forces of the dampers are derived and compared. It was shown that design equations are fairly accurate. As the height of the dampers increases, their effective stiffness and damping reduces and the dampers behavior leans towards flexural behavior. Based on cyclic and pushover analysis, Steel Plate Dampers (SPD) have the highest stiffness and energy dissipation. Also, SPD and Double Pipe Dampers (DPD) are the most suitable to reach a demanded stiffness, damping and have the most stable performance. At the end of the paper, a list of conclusions is presented.